ANTIBACTERIAL ACTIVITY OF PAPUYU FISH SCALE CHITOSAN (Anabas testudineus) AGAINST Staphylococcus aureus - Aila At-Thoyyar; Muhammad Yanuar Ichrom Nahzi; Dewi Puspitasari; Didit Aspriyanto; Juliyatin Putri Utami (FKG ULM, 2024)
Backgrounds: Pulp disease due to caries can be treated through endodontic treatment, which aims to eliminate bacteria in the root canal so microorganisms cannot multiply. Staphylococcus aureus is a resistant microorganism causing root canal treatment failure. Chlorhexidine as a gold standard cannot remove biofilm and other organic debris. Utilization of nature, chitosan of papuyu fish scales (Anabas testudineus) has antibacterial properties that can be an alternative root canal irrigation material. Purpose: Analyze the antibacterial activity of chitosan of papuyu fish scales against Staphylococcus aureus based on the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Methods: This research is a true experimental design with posttest only with control group design. The research groups were chitosan of Papuyu fish scales with concentrations of 25%, 50%, 75%, 100%, chlorhexidine gluconate 2% (positive control), and aquadest (negative control) with 6 repetitions. Results: The MIC value in the One-Way ANOVA test showed a significant difference (p<0.05). Data analysis followed by Post Hoc Games-Howell test showed all treatment groups had significant differences between each other (p<0.05). The MBC value in the Kruskal Wallis test shows that there is a significant difference (p<0.05). Data analysis followed by MannWhitney test showed significant differences between each other (p<0.05) except for the group of papuyu fish scale chitosan 25% concentration against papuyu fish scale chitosan 50% concentration, papuyu fish scale chitosan 100% concentration against chlorhexidine gluconate 2% (p>0.05). Conclusion: There is a difference in the antibacterial activity of chitosan of Papuyu fish scales concentrations of 25%, 50%, 75%, 100%, chlorhexidine gluconate 2% (positive control) and aquadest (negative control) against Staphylococcus aureus bacteria.